Efficacy and safety of adjunctive antiseizure medications for dravet syndrome: A systematic review and network meta-analysis - Wu, Jianhua; Zhang, Liu; Zhou, Xi; Wang, Jiajun; Zheng, Xiangyi; Hu, Hankun; Wu, Dongfang (Frontiers in Pharmacology, 2022)
Purpose: Recently, the U.S. Food and Drug Administration (FDA) approved stiripentol, cannabidiol, and fenfluramine to treat patients with Dravet syndrome (DS). Moreover, soticlestat was determined as a promising new drug for the treatment of DS as it has good efficacy and safety. However, the efficacy and safety of these drugs have not yet been evaluated in “head-to-head” trials. This study aimed to compare and evaluate the efficacy and safety of these adjunctive antiseizure medications in the treatment of DS. Methods: We searched in PubMed, Embase, Cochrane Library, and Web of Science databases for randomized controlled trials (RCTs) and open-label extension (OLE) studies in patients with DS. We performed a random-effect meta-analysis of OLE studies and a network meta-analysis for RCTs to evaluate the efficacy and safety of antiseizure medications in the treatment of DS. Primary efficacy outcomes were defined as a ≥50% reduction in seizure frequency compared with baseline. Furthermore, safety evaluation indicators were defined as the incidence of adverse events (AEs) and serious adverse events (SAEs) during treatment. Relative ranking was assessed using the surface under the cumulative ranking curve (SUCRA) probabilities. Results: Seven RCTs involving four antiseizure medications (stiripentol, cannabidiol, fenfluramine, and soticlestat) and a total of 634 patients were included in the analysis. According to the SUCRA results, all four drugs significantly reduced the frequency of seizures compared with the placebo. Soticlestat was the most likely to reduce seizure frequency by ≥50% compared to the baseline [risk ratio (RR): 19.32; 95% confidence interval (CI): 1.20–311.40], followed by stiripentol and fenfluramine. Stiripentol was ranked highest for the near percentage reduction in the seizure rate from baseline [RR: 12.33; 95% CI: 1.71–89.17] and the occurrence of any treatment-emergent adverse events [RR: 3.73; 95% CI: 1.65–8.43] and serious adverse events [RR: 4.76; 95% CI: 0.61–37.28]. A total of ten OLE studies containing 1,121 patients were included in our study. According to the results of the meta-analysis, the order of probability of reducing seizure frequency by ≥50% was fenfluramine (0.715, 95% CI: 0.621–0.808), stiripentol (0.604, 95% CI: 0.502–0.706), cannabidiol (0.448, 95% CI: 0.403–0.493). And the probability of occurrence of AEs is ranked as fenfluramine(0.832, 95% CI: 0.795–0.869), cannabidiol (0.825, 95% CI:0.701–0.950), stiripentol (0.823, 95% CI: 0.707–0.938), soticlestat (0.688, 95% CI: 0.413–0.890). Conclusion: According to the results of indirect comparison of efficacy and safety, cannabidiol is slightly inferior to the other three antiseizure medications in terms of efficacy and safety. Soticlestat, fenfluramine, and stripentol may have little difference in efficacy, but soticlestat and fenfluramine are safer. Soticlestat is probably the best adjunctive antiseizure medication, followed by fenfluramine. This conclusion is consistent with the comparison of long-term efficacy and safety.